Shaping the Future of Water for Agriculture : A Sourcebook for Investment in Agricultural Water Management - World Bank (Washington, DC: World Bank, 2012)
Agricultural water management is a vital practice in ensuring reduction, and environmental protection. After decades of successfully expanding irrigation and improving productivity, farmers and managers face an emerging crisis in the form of poorly performing irrigation schemes, slow modernization, declining investment, constrained water availability, and environmental degradation. More and better investments in agricultural water are needed. In response, the World Bank, in conjunction with many partner agencies, has compiled a selection of good experiences that can guide practitioners in the design of quality investments in agricultural water. The messages of this publication center around the key challenges to agricultural water management, specifically: building policies and incentives; designing institutional reforms; investing in irrigation systems improvement and modernization; investing in groundwater irrigation; investing in drainage and water quality management; investing in water management in rain-fed agriculture; investing in agricultural water management in multipurpose operations; coping with extreme climatic conditions; and assessing the social, economic, and environmental impacts of agricultural water investments.